The Gendered Economics of Synchronized Retirement. (August 2018) - Gustafson, Per
Women generally receive lower pensions than men, and research on gender and pensions has identified a number of factors underlying this pattern. The present article examines one factor that has largely gone unnoticed—synchronized retirement. In most married couples, the husband is older than his wife, yet many couples prefer to retire together. At the same time, pension systems are increasingly designed to discourage early retirement and reward late retirement. If younger wives and older husbands tend to synchronize their retirement, this may reinforce gendered income inequalities among older persons. Analyses of register data on Swedish married couples provide empirical support for this argument. Comparisons of their pre- and postretirement incomes show that women who synchronized retirement with their husbands had, in relative terms, lower postretirement incomes than other women, whereas men who synchronized had higher postretirement incomes than other men.